2011
DOI: 10.1186/1743-422x-8-559
|View full text |Cite
|
Sign up to set email alerts
|

An overview of human prion diseases

Abstract: Prion diseases are transmissible, progressive and invariably fatal neurodegenerative conditions associated with misfolding and aggregation of a host-encoded cellular prion protein, PrPC. They have occurred in a wide range of mammalian species including human. Human prion diseases can arise sporadically, be hereditary or be acquired. Sporadic human prion diseases include Cruetzfeldt-Jacob disease (CJD), fatal insomnia and variably protease-sensitive prionopathy. Genetic or familial prion diseases are caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 83 publications
2
116
0
22
Order By: Relevance
“…As the illness progresses, mental deterioration becomes pronounced and involuntary movements, blindness, weakness of extremities, and coma may occur. 79 Since this is a different clinical picture from Nodding Syndrome, a prion infection is an unlikely etiology for Nodding Syndrome.…”
Section: Infectious Agents Prionsmentioning
confidence: 96%
“…As the illness progresses, mental deterioration becomes pronounced and involuntary movements, blindness, weakness of extremities, and coma may occur. 79 Since this is a different clinical picture from Nodding Syndrome, a prion infection is an unlikely etiology for Nodding Syndrome.…”
Section: Infectious Agents Prionsmentioning
confidence: 96%
“…A plausible route for interspecies transmission of prion diseases is via breach of mucosal surfaces during ingestion of infectious prions found in carcasses, their by-products, and in the environment. Precedence for prion trans-species transmission has been well documented with vCJD, FSE, and TME (4,33). Studies have also demonstrated that prion diseases can be orally transmitted to many species: i.e., CWD to voles (34), Peromyscus mice (34), and ferrets (35), scrapie to squirrel monkeys (36) and hamsters (37)(38)(39)(40), BSE to sheep (41)(42)(43), goats (41), cynomolgus macaques (44,45), and lemurs (46), and CJD and Kuru to squirrel monkeys (36), with some requiring prior in vivo or in vitro adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…1 About 85% of all CJD cases are sporadic, 10-15% are inherited and less than 1% is acquired. 2 Normal cellular prion protein (PrP C ) is encoded by PRNP gene that locates at chromosome 20 of humans.…”
Section: Introductionmentioning
confidence: 99%